They Die Strangers: Stories from Yemen: Examining the Postcolonial Narratives of Emigration in Yemen through 'They Die Strangers' (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This article evaluates thenovel They Die Strangers  (1972)  by the  Yemeni  novelist Mohammed  Ahmed  Abdul Wali  as  a postcolonial narrative of emigration inwhich the writer argues about what is called the ideology of return. Anemigrant himself, the writer discusses the impact of long- term  emigration on  the  individual, his  family  and the  society  as a  whole.  The discussion, using a postcolonialperspective, covers issues related to the construction of  the  Yemeni  identity, body  politics,  the Yemeni  farmers‟   dream   and the representation  of  women focusing  on  the body-land  association.  The discussion concludes with considering the novel as a parody againstthose who migrate leaving their women and their land behind, only to live anddie as strangers.